Literatur Review Faktor Resiko Penyebab Terjadinya Hipertensi Pada Kehamilan - Fuad Amjad; Anna Sari Dewi; Muskamal Tabbate (2024)
Hypertension in pregnancy is a common complication of pregnancy and the main cause of maternal and perinatal morbidity and mortality in the world. This includes chronic hypertension, gestational hypertension, preeclampsia/eclampsia. The incidence of hypertension in pregnancy can be influenced by several factors (multiple causation). Maternal age (<20 or ≥ 35 years), primigravida, nulliparity and increased Body Mass Index (BMI) are risk factors for hypertension in pregnancy. The impact on pregnancy and health greatly influences the conditions and circumstances during pregnancy. The aim of this paper is to explain the risk factors that can cause hypertension during pregnancy. This research uses the review article method. The data source for this research comes from published research results. Based on the results of the article review, it can be concluded that hypertension in pregnancy can be influenced by several factors such as age, BMI, primigravida